PENINGKATAN KINERJA PENDIDIK PAUD DALAM PENGEMBANGAN KEMAMPUAN KINESTETIK - Andun Sudijandoko (Jurnal Cakrawala Pendidikan, 2011)
Abstract: The Improvement of ECE Educators’ Performance in Developing the Kinesthetic Quotient. This study aims to improve the performance of Early Childhood Education (ECE) educators at the TAPAS Al-Ikhlas BPPNFI Regional IV Surabaya so that they are capable of developing children’s kinesthetic qoutient through the concepts of ECE and kinestetic teachinglearning. This study was a classroom action research study. The data were collected through interviews, observations, and documents and were analyzed by means of data reduction, data display, data verification, and conclusion drawing. The findings showed that: (1) before the action was implemented, the kinesthetic teaching-learning model was teacher-centered, the educators did not understand kinesthetic learning concept and learning psychology, the classroom management was not well implemented, and the teaching style was monotonous, (2) after the action was implemented, the educators’ teaching skills improved, they employed a variety of teching styles, they understood ECE concepts better, and they were willing to accept changes and committed to making changes. Keywords: Early Childhood Education, Kinesthetic Qoutient